Does more stringent environmental regulation induce or reduce technology adoption? When the rate of technology adoption is inverted u-shaped - Grischa Perino; Till Requate (Kiel University, Department of Economics, 2012)
We show that for a broad class of technologies the relationship between policy stringency and the rate of technology adoption is inverted U-shaped. This happens when the marginal abatement cost (MAC) curves of conventional and new technologies intersect, which invariably occurs when emissions are proportional to output and technological progress reduces emissions per output. This outcome does not result from policy failure. On the contrary, in social optimum, the relationship between the slope of the marginal damage curve and the rate of technology adoption is also inverted U-shaped. Under more general conditions, these curves can look even more complicated (e.g. such as inverted W-shaped).
Keywords: Q55; Q52; Q58; H23; O33; 330; induced diffusion; environmental policy; Umweltpolitik; Umwelttechnik; Innovationsdiffusion; Theorie